2013
DOI: 10.1371/journal.pone.0081507
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of Retinal ON Bipolar Cells Induced by Serum Including Autoantibody against TRPM1 in Mouse Model of Paraneoplastic Retinopathy

Abstract: The paraneoplastic retinopathies (PRs) are a group of eye diseases characterized by a sudden and progressive dysfunction of the retina caused by an antibody against a protein in a neoplasm. Evidence has been obtained that the transient receptor potential melastatin 1 (TRPM1) protein was one of the antigens for the autoantibody against the ON bipolar cells in PR patients. However, it has not been determined how the autoantibody causes the dysfunction of the ON bipolar cells. We hypothesized that the antibody ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Although DDD does not always correlate with the presence and severity of LBP, an IVD-related problem is generally accepted to be the most common cause of LBP (Schwarzer et al, 1995), as degenerated IVDs are frequently invaded by newlyformed nociceptive nerves (Sivan et al, 2014;Urban et al, 2004). Discogenic nociceptive pain is caused by a neuronal sensitisation, due to internal IVD disruption (Roberts et al, 2006), while neuropathic pain arises from neuronal damage and inflammation caused by IVD-related compression of nerve roots (Cramer and Darby, 1997;Ito and Creemers, 2013).…”
Section: Degenerative Joint Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although DDD does not always correlate with the presence and severity of LBP, an IVD-related problem is generally accepted to be the most common cause of LBP (Schwarzer et al, 1995), as degenerated IVDs are frequently invaded by newlyformed nociceptive nerves (Sivan et al, 2014;Urban et al, 2004). Discogenic nociceptive pain is caused by a neuronal sensitisation, due to internal IVD disruption (Roberts et al, 2006), while neuropathic pain arises from neuronal damage and inflammation caused by IVD-related compression of nerve roots (Cramer and Darby, 1997;Ito and Creemers, 2013).…”
Section: Degenerative Joint Diseasesmentioning
confidence: 99%
“…TRPV1 is activated by acidic pH (Dhaka et al, 2009), which is an important factor in chondrocyte and IVD homeostasis. Lactic acid accumulates in degenerative joints and IVDs as a result of impaired fluid transport (Roberts et al, 2006;Urban et al, 2004), altering the cellular repair capacity and promoting pain (Le Maitre et al, 2007). As a putative sensor for acidic pH, over-stimulated or up-regulated TRPV1 can be possibly involved in the responses of chondrocytes and IVD cells to acidity.…”
Section: Trpml2 -/-mentioning
confidence: 99%
See 1 more Smart Citation
“…Without these processes, it was difficult to differentiate the patients’ serum samples from the few control serum samples assessed in parallel. In fact, we experienced similar difficulties in obtaining reliable staining images of the bipolar cells when using other serum samples from TRPM1‐associated autoimmune retinopathy in a previous study . The technician in our lab found that performing the required optimization was not trivial, unlike Western blotting, which requires minimal effort.…”
mentioning
confidence: 85%
“…The retinas were used for histologic analyses, as previously described in detail. 22 The optic nerves were approximately 1 to 5 mm posterior to the sclera. They were fixed in 1% osmium tetroxide in phosphate-buffered saline.…”
Section: Optic Nerve Tissues and Retinal Sectionsmentioning
confidence: 99%